Effect of human‐controlled hydrological regime on the source, transport, and flux of particulate organic carbon from the lower Huanghe (Yellow River). Issue 8 (19th March 2015) - Hu, Bangqi; Li, Jun; Bi, Naishuang; Wang, Houjie; Wei, Helong; Zhao, Jingtao; Xie, Luhua; Zou, Liang; Cui, Ruyong; Li, Song; Liu, Ming; Li, Guogang
Abstract Evaluating the role of fluvial transfer of terrestrial organic carbon (OC) and subsequent burial in the global carbon cycle requires the sources and fluxes of fluvial OC to be assessed, which remains poorly constrained in the Huanghe (Yellow River). Here, we report the elemental, stable isotopic, and radiocarbon activity of particulate organic carbon (POC) sampled at the outlet of Huanghe in 2012–2013. We show that the Huanghe riverine POC can be explained by binary mixing of fossil (POCfossil) and non‐fossil (POCnon‐fossil) components, the former may reach 40% of the total POC. The Huanghe POCnon‐fossil is mostly sourced from C3 plants, with a mean residence time of c. 2200 years. The current human‐controlled hydrological regime strongly influenced the POC sources, transport modes, and fluxes. In 2012–2013, the Huanghe delivered 0.73 Tg (1 Tg = 1012 g) of POC to the sea, and about 28% of the annual POC flux occurred within a short human induced flood event. Globally, the Huanghe should be one of the largest rivers in the transfer and re‐burial of fossil OC. However, the fate of Huanghe fossil OC is still unconstrained and needs to be further investigated. Copyright © 2015 John Wiley & Sons, Ltd.